Barriers Pushed Aside: Insights on Career and Family Success from Women Leaders in Academic Otolaryngology. (August 2019) - Meyer, Tanya K.; Bergmark, Regan; Zatz, Marcy; Sardesai, Maya G.; Litvack, Jamie R.; Starks Acosta, Anne
Objective: Although the literature adequately identifies the current gender inequality that exists in academic otolaryngology and describes the barriers to advancement of women in academic medicine, there is little information regarding the daily details of how successful women in academic otolaryngology achieve work-life balance. This study was designed to better understand how women in academic otolaryngology achieve work-life balance while negotiating family and childrearing commitments, clinical workload, and scholarly activity, as well as to highlight coping strategies and behaviors that women have used to achieve these successes. Study Design: Qualitative research design. Methods: Thirteen successful women in academic otolaryngology with children were recruited using a networking/snowball sampling methodology to participate in a semistructured qualitative interview about the daily process of work-life balance in an academic otolaryngology practice. A focus group of 7 additional participants was held to validate critical topics/themes. Results: Four broad categories of findings emerged from the study: (1) participants' strong commitment to academic medicine, (2) the fluid/elusive nature of work-life balance, (3) specific approaches to successfully managing home life, and (4) insights related to achieving psychoemotional health. Conclusions: The conflicting demands between home and professional life are one of the barriers to recruiting, promoting, and retaining women in academic otolaryngology. Fostering a better environment for work-life balance is critical to promote the advancement of women in otolaryngology and otolaryngology leadership.